The impact of intergenerational transfers on the distribution of wealth: An international comparison - Charles Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2024)
In this paper, I analyze detailed data on intergenerational transfers in 4 countries (China, India, Japan, and the United States) from the "Japan Household Panel Survey on Consumer Preferences and Satisfaction (JHPS-CPS)" which has been conducted by the Institute of Social and Economic Research of Osaka University in these 4 countries since 2003, in order to shed light on the impact of intergenerational transfers on household wealth disparities and on possible reasons for the substantial differences in household wealth disparities among the 4 countries. Almost all of the evidence I present suggests that intergenerational transfers have a disequalizing impact on household wealth disparities and promote the transmission of household wealth disparities from generation to generation in all 4 countries although the magnitude of these effects varies considerably from country to country. Moreover, the evidence I present sheds considerable light on possible reasons for the substantial differences in household wealth disparities among the 4 countries.
Keywords: D12; D31; D64; E21; E24; J16; 330; bequests; estates; household wealth; inheritances; inter vivos transfers; intergenerational mobility; intergenerational transfers; wealth disparities; wealth distribution; wealth inequality; China; India; Japan; United States